Addressing the inappropriate use of force by police in the United States and beyond: A behavioral and social science perspective. Issue 5 (5th May 2021) - Boxer, Paul; Brunson, Rod K.; Gaylord‐Harden, Noni; Kahn, Kimberly; Patton, Desmond U.; Richardson, Joseph; Rivera, Luis M.; Smith Lee, Jocelyn R.; Staller, Mario S.; Krahé, Barbara; Dubow, Eric F.; Parrott, Dominic; et al.
Abstract: Recent high‐profile incidents involving the deadly application of force in the United States sparked worldwide protests and renewed scrutiny of police practices as well as scrutiny of relations between police officers and minoritized communities. In this report, we consider the inappropriate use of force by police from the perspective of behavioral and social science inquiry related to aggression, violence, and intergroup relations. We examine the inappropriate use of force by police in the context of research on modern policing as well as critical race theory and offer five recommendations suggested by contemporary theory and research. Our recommendations are aimed at policymakers, law enforcement administrators, and scholars and are as follows: (1) Implement public policies that can reduce inappropriate use of force directly and through the reduction of broader burdens on the routine activities of police officers. (2) For officers frequently engaged in use‐of‐force incidents, ensure that best practice, evidence‐based treatments are available and required. (3) Improve and increase the quality and delivery of noncoercive conflict resolution training for all officers, along with police administrative policies and supervision that support alternatives to the use of force, both while scaling back the militarization of police departments. (4) Continue the development and evaluation of multicomponent interventions for police departments, but ensure they incorporate evidence‐based, field‐tested components. (5) Expand research in the behavioral and social sciences aimed at understanding and managing use‐of‐force by police and reducing its disproportionate impact on minoritized communities, and expand funding for these lines of inquiry.